Impaired Recognition of Facial Emotion in Patients With Parkinson Disease Under Dopamine Therapy. (September 2020) - Palmeri, Rosanna; Buono, Viviana Lo; Bonanno, Lilla; Allone, Cettina; Drago, Nancy; Sorbera, Chiara; Cimino, Vincenzo; di Lorenzo, Giuseppe; Bramanti, Alessia; Marino, Silvia
Introduction: Parkinson disease (PD) is a neurodegenerative disorder characterized by motor and nonmotor symptoms. The impaired ability to recognize facial emotion expressions represents an important nonmotor symptom. The aim of this study is to investigate the ability in recognizing facial emotion expressions in patients with PD under dopamine replacement therapy. Methods: Thirty medicated patients with PD and 15 healthy controls (HC) were enrolled. All participants performed the Ekman 60-Faces test for emotional recognition. All patients underwent a neuropsychological evaluation for global cognitive functioning, depression, and anxiety. Results: Patients with PD were impaired in recognizing emotions. Significant differences between PD and HC were found in Ekman 60-Faces test scores ( P < .001), and in Ekman 60-Faces test subscales, in particular, sadness, fear, disgust, anger, and surprise ( P < .001). Conclusions: The nigrostriatal dopaminergic depletion seems to determine emotional information processing dysfunction. This relevant nonmotor symptom could have consequences in daily living reducing interactions and social behavioral competence.